GENDER DYNAMICS ON SPEAKING INTERACTION IN THE COLLEGE CLASSROOM - Apriyanto, Sigit; Anum, Adelina (JURNAL SMART, 2018)
Objectives of this research are to describe the gender dynamics, the influence of lecturers to the studentâs interaction and the influence of classmates to the studentsâ interaction in speaking interaction. The population of this research are the third semester students in Graduate School, Ahmad Dahlan University. Triangulation method is used to address the same set of research. The research found that personalities of group members appeared to affect group dynamics positively. Then, an authoritarian teaching has a negative effect on the classroom climate. The lecturersâ interaction is perceived to affect the studentsâ interaction in the classroom and on their learning.